(3MdjI GdYQhS aj eMGSf GdWQhSs - (3CMeO CafOj GdcGJHs
(3ChdgG (B:s
(3CeG HYO(B: (3aEfj bjd GdBf hajeG eVi ef GdChGf heQ ef GdReGf, LeYJ HYV ChQGb ajeG MSf hdg hQGb ef WjH GdecGJHGJ hGdEfTGA hGdeQGSdGJ hSejJgG agj ZGjI GdNJUGQ NGdjI ef GdJWhjd hGdEcKGQ s
(3BNQgG (B:s
(3adh QCi HMQ BOGH GdUai dGSJYPH hUaG, aedC GdbdhH SQhQkG HhahOg, hTQM UOhQ eMHjg HhQhOg, abGe GdeMH Mjf hQhOg ebGeG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B266 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3COH JjehQ (B246) s
Keywords: (3GdCOHs